Targeted p53 activation by saRNA suppresses human bladder cancer cells growth and metastasis. Issue 1 (December 2016) - Wang, Chenghe; Ge, Qiangqiang; Zhang, Qingsong; Chen, Zhong; Hu, Jia; Li, Fan; Ye, Zhangqun
Abstract Background Previous study showed that dsP53-285 has the capacity to induce tumor suppressor gene p53 expression by targeting promoter in non-human primates' cells. And it is well known that TP53 gene is frequently mutant or inactivated in human bladder cancer. Hereby, whether this small RNA can activate the expression of wild-type p53 and inhibit human bladder cancer cells remains to be elucidated. Methods Oligonucleotide and lentivirus were used to overexpress dsP53-285 and dsControl. Real-time PCR and western blot were used to detect genes' mRNA and protein expression, respectively. Cell proliferation assay, colony formation, flow cytometry, transwell assay and wound healing assay were performed to determine the effects on bladder cancer cells proliferation and migration/invasionin vitro . Animal models were carried out to analyze the effects on cells growth and metastasisin vivo . Results Transfection of dsP53-285 into human bladder cancer cell lines T24 and EJ readily activate wild-type p53 expression by targeting promoter. Moreover, dsP53-285 exhibited robust capacity to inhibit cells proliferation and colony formation, induce cells G0/G1 arrest, suppress migration and invasion. Besides, the Cyclin-CDK genes (Cyclin D1 and CDK4/6) were down-regulated and the EMT-associated genes (E-cadherin, β-catenin, ZEB1 and Vimentin) were also expressed inversely after dsP53-285 treatment. In addition, dsP53-285 could also significantly suppress the growth of bladder cancer xenografts and metastasis in nude mice. Most importantly, the anti-tumor effects mediated by dsP53-285 were mainly achieved by manipulating wild-type p53 expression. Conclusion Our findings indicate that the dsP53-285 can upregulate wild-type p53 expression in human bladder cancer cells through RNA activation, and suppresses cells proliferation and metastasisin vitro andin vivo .